Effects of dapagliflozin on heart rate variability, cardiac function, and short-term prognosis in early-onset post-myocardial infarction heart failure - Le Zhou; Mingyuan Niu; Wei Chen; Qian Hu; Yi Chen; Xiaohong Geng; Jiani Gu (Frontiers in Cardiovascular Medicine)
ObjectiveTo investigate the effects of dapagliflozin, in addition to standard therapy, on heart rate variability (HRV), soluble growth stimulation expressed gene 2 protein (sST2), N-terminal pro B-type natriuretic peptide (NT-proBNP), and echocardiographic parameters in patients with early-onset post-myocardial infarction heart failure (HF).MethodsA total of 98 patients with early-onset post-myocardial infarction HF were enrolled and randomly divided into a control group (n = 48, receiving standard therapy) and an observation group (n = 50, receiving standard therapy plus dapagliflozin 10 mg daily). HRV, cardiac function, and echocardiographic parameters were measured at baseline and after 24 weeks of treatment. Short-term prognosis and adverse events were also monitored.ResultsCompared with the control group, the observation group showed significantly greater improvements in SDNN and SDANN (P < 0.05). Significant improvements were also observed in sST2 and NT-proBNP levels in the observation group compared to the control group (P < 0.05). Additionally, echocardiographic parameters, including EF, LVESD, LVEDD, IVST, LVMI, and E/e’, showed greater improvement in the observation group (P < 0.05). The incidence of major adverse cardiovascular events was lower in the observation group (P < 0.05). Multivariate logistic regression model revealed that dapagliflozin use was independently associated with a reduced risk of MACE (OR = 0.265, 95% CI: 0.097–0.724, P = 0.010).ConclusionEarly administration of dapagliflozin 10 mg, in addition to standard therapy, can improve autonomic function, cardiac function, and short-term prognosis in patients with early-onset post-myocardial infarction heart failure.